Quaternary nannoplankton in the Northeast Java Basin - Kapid, Rubiyanto; Santoso, Wahyu Dwijo; Insani, Halmi (Ikatan Ahli Geologi Indonesia, 2021)
In Indonesia, nannofosils are commonly used for age estimation on Miocene marine sediment, but they are rarely performed on Quaternary sediment. This paper introduces two nannofossil biozones, Martini (1971) and Backman et al. (2012) and the comparison between the two biozones. An uninterrupted interval of marine sediments was described and picked for quantitative nannoplankton analysis. The samples were taken from Ledok Formation to Lidah Formation in Pati Region, Northeast Java Basin. The samples were prepared by quick smear slides method and and analyzed by quantitative field of view method. Martini (1971) biozone can be used to subdivide the Late Miocene–Pleistocene sediments into 5 biozones, but Backman et al. (2012) can be used to classify the same sediments into 8 biozones. The biozone subdivision from Backman et al. (2012) is more detailed than that of Martini (1971) because an updated dating and biozone in the three new dating zone data.